PHOTOVOLTAIC BASED ELECTRIC VEHICLE CHARGER FOR CUSTOMER ADAPTIVE CHARGING STATION - S, Ishwarya; K, Arunkumar; D , Nithosh; B, Thandeshwarar (International Journal of Psychosocial Rehabilitation, 2024)
This paper describes the multifunction EV charger for house hold applications. solar and grid vehicle charger scheme is implemented for charging of electric vehicle system. EV charger scheme is implemented using RFID reader to analysis vehicles for charging and would allow EV charging to be conducted. RFID reader is used for analysis battery charging price analysis